Antimicrobial and Antivirulence Action of Eugenia brejoensis Essential Oil in vitro and in vivo Invertebrate Models - Bezerra Filho, Clovis Macêdo; da Silva, Luís Cláudio Nascimento; da Silva, Márcia Vanusa; Løbner-Olesen, Anders; Struve, Carsten; Krogfelt, Karen Angeliki; Correia, Maria Tereza dos Santos; Vilela Oliva, Maria Luiza (Frontiers in Microbiology, 2020)
Eugenia brejoensis L. (Myrtaceae) is an endemic plant from caatinga ecosystem (brazilian semi-arid) which have an essential oil (EbEO) with reported antimicrobial activity. In this work, in vitro and in vivo models were used to characterize the inhibitory effects of EbEO in relation to Staphylococcus aureus. EbEO inhibited the growth of all tested S. aureus strains (including multidrug resistance isolates) with values ranging from 8 to 516 μg/ml. EbEO also synergistically increased the action of ampicillim, chloramphenicol and kanamycin. The treatment with subinhibitory concentrations (Sub-MIC) of EbEO decreased S. aureus hemolytic activity and its ability to survive in human blood. EbEO strongly reduced the levels of staphyloxanthin, an effect related to increased susceptibility of S. aureus to hydrogen peroxide. The efficacy of EbEO against S aureus was further demonstrated using Caenorhabditis elegans and Galleria mellonella. EbEO increased the lifespan of both organisms infected by S. aureus, reducing the bacterial load. In addition, EbEO reduced the severity of S. aureus infection in G. mellonella, as shown by lower levels of melanin production in those larvae. In summary, our data suggest that Eugenia brejoensis essential oil is a potential source of lead molecules for development of new therapeutic alternatives against S. aureus.